EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD) GOALS: PERSEPSI GURU SEKOLAH DASAR DI WILAYAH IKN - Suhartini, Erna; Haerani, Rosita; Ardiyanti, Mega; Nanda Mawar Raihanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Indonesian government has designated the IKN in East Kalimantan as the most sustainable city in the world, a symbol of the identity of the Indonesian nation, and a driver of the future economy (KLHK, 2022). On the other hand, the challenges faced in the transmission of the IKN include the threat of environmental damage including the potential for educational disparities. The existence of the idea of ​​SD through education must be optimized, because quality education in the SDGs dimension will equip individuals, society, and government to live and act with an understanding of the environment, society, and economy (Suwarto et al., 2021). To achieve sustainability through education, there is a need to develop ESD-aware teachers. This study will quantitatively interpret the perceptions of elementary school teachers in the IKN area towards ESD (Knowledge, Attitude and skill). The study involved 104 elementary school teachers from 5 cities/regencies in the IKN area and its buffer zones. This study used an anonymous questionnaire that captured teacher perceptions using a five-point Likert scale questionnaire developed with a quetionerry using Alpha Cronbach. The results show that teachers have a positive attitude towards ESD and a willingness to implement ESD in their teaching. Teachers' skills in practicing ESD-based teaching are in the high category, but need to be improved in terms of encouraging creativity in completing tasks and accepting various possible conclusions. Teachers' knowledge is quite high, but they do not yet have a complete understanding of ESD such as the concept of harmony with nature, three ESD topics and ESD interdisciplinary. These findings may be useful as a basic survey in implementing teacher training programs and developing modules and teaching media that are integrated with ESD in the scope of elementary education.